PROTOTIPE MASHUP LAYANAN INFORMASI PUBLIK PERPUSTAKAAN BPPT - Parlina, Anne; Ardiansyah, Firman; Budiarto, Hary (BACA: Jurnal Dokumentasi dan Informasi, 2014)
The Agency for the Assessment and Application of Technology Library has the duty to provide public information services to the community. However, this public information was scattered in several different websites. In this study, mashup technology was used to collect and combine content from external sources. Information architectureand prototype of public information service mashup were designed and created. The result showed that mashup technology can be used to create a new service that easily community to find the public information without open many websites at the same time.